Antibacterial activity of essential oils potentially used for natural fiber pantiliner textronic system development. (2017) - Frydrysiak, Emilia; Śmigielski, Krzysztof; Zabielska, Julia; Kunicka-Styczyńska, Alina; Frydrysiak, Michał
Abstract: An impact of the essential oils applied on a cellulose fiber on the selected bacteria strains was investigated. Five essential oils: Matricariachamomilla L., Salvia officinalis L., Salvia lavandulaefolia Vahl., Juniperuscommunis L. and Thymus vulgaris L. were tested against Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus epidermidis and Staphylococcus saprophyticus . For the pantiliner of textronics system for prophylactic and support treatment of the lower urinary tract inflammation, the only Thymus vulgaris essential oil was chosen as the most effective against bacteria associated with urinary tract infections.